ANALISIS KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KANTOR DESA (STUDI KASUS: DESA SUMBER RAHAYU, KABUPATEN MUARAENIM): - Umi Purwanti; Isma Nirmala; Yuliana Yuliana; Amir Mahmud; Amalia Mustikatamara (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study aims to analyze the quality of population administration services at the Sumber Rahayu Village Office, Rambang District, Muara Enim Regency. Population administration services include the management of ID card introductions, Family Cards, domicile letters, birth certificates, and death certificates which are the main needs of the village community. This study has a novelty in the focus of the study that not only assesses the quality of services based on the SERVQUAL dimension, but also analyzes the influence of the readiness of village apparatus and administrative systems on the effectiveness of public services at the village level. The research uses a qualitative method with a descriptive approach. Data was obtained through interviews, observations, and documentation with informants consisting of village and community officials. Data analysis uses the Miles and Huberman model through data reduction, data presentation, and conclusion drawn. The results of the study show that the quality of population administration services in Sumber Rahayu Village in general is quite good, especially in the aspects of responsiveness and empathy of village officials. However, services have not run optimally because there are still obstacles in the form of limited human resources, inadequate service facilities, and a manual administrative system. Therefore, it is necessary to increase the capacity of apparatus, improve service facilities, and develop a digital-based administrative system to improve the quality of public services in the village.